2019
DOI: 10.2147/cmar.s200907
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Sp1 contributes to radioresistance of cervical cancer through targeting G2/M cell cycle checkpoint CDK1</p>

Abstract: Background/aims Radioresistance remains a significant obstacle in the therapy of cervical cancer, and the mechanism of it is still unclear. We aimed to investigate the role of specificity protein 1 (Sp1) in radioresistance of cervical cancer. Methods Sp1 was examined immunohistochemically on tissues from 36 human cervical cancer patients. We used RT-qPCR and Western blot to examine the expression of Sp1 in irradiated cervical cancer cell lines SiHa and HeLa. The role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Activation of the CDK1-TFCP2L1 pathway stimulated cell proliferation, self-renewal and invasion in human aggressive bladder cancer. 31 Deng 32 reported that the up-regulation of CDK1 inhibited the G2/M phase block and promoted cervical cancer resistance to radiotherapy. CDK1 was also found to be stably activated by CDK1-KCTD12 interaction in BRAF-mutated colon cancer models resistant to Vemurafenib.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the CDK1-TFCP2L1 pathway stimulated cell proliferation, self-renewal and invasion in human aggressive bladder cancer. 31 Deng 32 reported that the up-regulation of CDK1 inhibited the G2/M phase block and promoted cervical cancer resistance to radiotherapy. CDK1 was also found to be stably activated by CDK1-KCTD12 interaction in BRAF-mutated colon cancer models resistant to Vemurafenib.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al. showed that high Sp1 expression levels were correlated to cervical cancer progression, and that knockdown of Sp1 significantly enhanced the cellular response to radiation by inducing G2/M arrest, suggesting that Sp1 might represent a potential therapeutic target in cervical cancer [126] . Tumour hypoxia is an important contributor to radioresistance.…”
Section: Genetic Regulation Of Mitochondria Energy Metabolism and Radmentioning
confidence: 99%
“…The induction of cell cycle arrest at the G2/M phase in tumor cells may be an effective strategy for enhancing the ionizing radiation effect against tumors [28]. Numerous recent studies have shown that increasing radiation-induced G2/M phase arrest in tumor cells can significantly increase the sensitivity of HNSCC, cervical cancer, and prostate cancer cells to ionizing radiation[29][30][31][32]. In the present study, the cell cycle detection results after irradiation showed that the proportion of cells in the G2/M phase in the CNE-2sh group was significantly higher than that in the control group cells, indicating that FANCD2 silencing significantly increased radiation-induced G2/M phase cell cycle arrest in the CNE-2 cells and enhanced their ionizing radiation sensitivity.Interestingly, in ionizing radiation sensitivity experiments involving bone marrow stromal cells and IL-3-dependent hematopoietic stem cells of FANCD2-deficient mice, Berhane et al found that the growth life of bone marrow stromal cells was shortened and showed strong radiation sensitivity and DNA damage involvement.…”
mentioning
confidence: 99%